Wind Energy Conversion System with Integrated Power Smoothing Capability based on an EVT-coupled Flywheel - Cendoya, Marcelo Gustavo (2024)
This paper presents a wind energy conversion system that integrates, in a compact form, both generation and power smoothing functions. The system is based on a vertical axis wind turbine (VAWT) and a low-speed flywheel that are coupled by an electric variable transmission (EVT). The EVT performs a dual function by simultaneously injecting power to the grid and regulating the power flow to the flywheel to smooth the power fluctuation caused by wind turbulences. The main advantages of the presented generation/smoothing topology are integrating two machines (generator and motor) in the same physical structure and the reduced power demanded by the converter that feeds the flywheel’s rotor. A theoretical analysis is carried out to determine an appropriate control law and flywheel sizing to satisfy a desired attenuation of the power fluctuation. Simulation results show an effective smoothing action, as the power fluctuation is reduced to an adequate level. In addition, the validity of the flywheel sizing procedure is verified.